Exploring the Green Purchase Intention of Generation Z personal care products: The Role of Environmental Consciousness, Consumer Attitudes, and Religiosity - Sari, Putri Ruspida; Hadi, Effed Darta (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to examine the impact of environmental consciousness on green purchasing intentions, as well as the mediating effect of consumer attitudes on the relationship between environmental consciousness and green purchasing intentions. Additionally, it investigates the moderating effect of religiosity on the relationship between consumer attitudes and green purchasing intentions among Generation Z in Indonesia regarding environmentally friendly personal care products. This study utilised quantitative methods, employing a survey administered through Google Forms for data collection. This study utilised a non-probability sampling method, specifically purposive selection, to select 349 respondents from Generation Z in Indonesia, with data analysed using Smart PLS software version 4.1.1.2. This study's findings indicate that environmental consciousness positively and significantly influences green purchasing intentions and consumer sentiments. Consumer attitudes exert a favorable and significant influence on green purchasing intentions and can mitigate the link between environmental consciousness and green purchase intentions. Nonetheless, religiosity exerts a negligible and insignificant influence on moderating the link between consumer views and intentions to purchase green products.